Viver de arte: percursos de formação e inserção socioprofissional de egressos de cursos de educação profissionalizante em artes, em Salvador, Bahia - Ivan Faria (2017)
The main purpose of the research project is to analyze the training process and socio-professional insertion of former students of vocational training in Music, Dance, Video and Photography, in the city of Salvador, Brazil. Even though it is an unstable and precarious labor field, the artistic sector and the so-called creative professions have attracted many young students, searching for greater fulfillment and identification in their work activities. The chosen empirical context is the city of Salvador, which stands out for being one of the most unequal capitals of Brazil. But at the same time, the city has invested in the culture of economy and in offering opportunities for artistic training at social projects, cultural associations, technical and undergraduate courses. Both the theoretical and epistemological framework seek to articulate structural, institutional and life contexts, using as references the sociology at the individual level and theories on plural socialization. The study adopted a methodology of qualitative approach, mixed with the support of quantitative data, conforming a total of 209 former students from three educational institutions (CEEP- Artes e Design, Escola de Dança da Funceb and Oi Kabum! Escola de Arte e Tecnologia), who answered online questionnaires and 9 of whom participated in in-depth interviews. The results show that students were submitted to different probations in the processes of artistic socialization and professional insertion. The socializing experiences promoted by families, churches, schools, social projects, courses of artistic training, institutions and networks, functioned as distinct supports for the constitution of artistic identities of the investigated subjects.